1978
DOI: 10.1029/jc083ic12p06123
|View full text |Cite
|
Sign up to set email alerts
|

Geostationary satellite observations of Gulf Stream meanders: Infrared measurements and time series analysis

Abstract: The infrared capabilities of the Geostationary Operational Environmental Satellite (Goes) are analyzed to obtain multiyear time histories of Gulf Stream meanders. Radiative transfer calculations using monthly mean profiles of atmospheric temperature and moisture are shown to overestimate cloud‐free equivalent soundings by 2–5 K. A simple relation is derived between temperature at the satellite, sea surface temperature, and transmissivity of the atmosphere at 11.6 μm, which allows an observer to determine if a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1980
1980
2007
2007

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…This topographic feature produces an eastward deflection in the Gulf Stream (Pietrafesa et al 1978;Rooney et al 1978;Brooks and Bane 1978), forming a quasi-permanent 10-50-km meander. It has also been reported that the lateral meanderings of the Gulf Stream undergo a dramatic "amplification" (Knauss 1969;Maul et al 1978;Bane and Brooks 1979;Hood and Bane 1983;Olson et al 1983) downstream from the CB. Accumulating evidence has suggested a regional difference in spatial scale of Gulf Stream meanders: south of the latitude of the CB cold-core frontal eddies tend to occur as smaller, elongated filaments (Lee and Mayer 1977;Lee et al 1981;Lee and Atkinson 1983) and north of CB frontal eddies tend to be considerably larger (Pietrafesa andJanowitz 1979, 1980;Bane and Brooks 1979;Pietrafesa and Janowitz 1980;Bane et al 1981;Bane 1981, 1983).…”
Section: Introductionmentioning
confidence: 95%
“…This topographic feature produces an eastward deflection in the Gulf Stream (Pietrafesa et al 1978;Rooney et al 1978;Brooks and Bane 1978), forming a quasi-permanent 10-50-km meander. It has also been reported that the lateral meanderings of the Gulf Stream undergo a dramatic "amplification" (Knauss 1969;Maul et al 1978;Bane and Brooks 1979;Hood and Bane 1983;Olson et al 1983) downstream from the CB. Accumulating evidence has suggested a regional difference in spatial scale of Gulf Stream meanders: south of the latitude of the CB cold-core frontal eddies tend to occur as smaller, elongated filaments (Lee and Mayer 1977;Lee et al 1981;Lee and Atkinson 1983) and north of CB frontal eddies tend to be considerably larger (Pietrafesa andJanowitz 1979, 1980;Bane and Brooks 1979;Pietrafesa and Janowitz 1980;Bane et al 1981;Bane 1981, 1983).…”
Section: Introductionmentioning
confidence: 95%
“…The atmospheric features have advection rates that are orders of magnitude greater than the oceanic rates. Hence Maul et al (1978) channel TIR data to minimize such misinterpretations. By this technique, the atmospheric processes disguised as oceanic ones could be eliminated.…”
Section: Methodsmentioning
confidence: 99%
“…Statistical methods using boat sample calibration are common for small-scale quantification of thermal plumes and estuarine surface temperatures (Worthington 1973). Deterministic methods are quite successful for determining the exitant radiation relationship to surface temperature, but are less successful in modelling a complex atmosphere in the thermal infrared portion of the spectrum (Maul et al 1978). Such methods often must rely on radiosonde atmospheric profiles of temperature and humidity.…”
Section: The Ocean Colormentioning
confidence: 99%